Pemberdayaan Ekonomi Masyarakat Desa Bilebante Berbasis Desa Wisata Perspektif Ekonomi Syari’ah - Jani, Bagus; Elbadriati, Baiq; Mulhimmah, Baiq Ratna (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study explores the implementation of Islamic economic concepts in community empowerment at DWH Bilebante. Through a qualitative approach, the research identifies that DWH Bilebante integrates values such as divinity, prophethood, governance, justice, and accountability in their efforts to enhance economic and social well-being of the community. These concepts not only emphasize fairness in the distribution of resources and opportunities but also promote honesty, transparency, and responsibility in economic activities. The study demonstrates that this approach successfully creates a balanced environment between material gain and spiritual well-being, fostering economically and socially resilient communities.